Do Immigrants Integrate Out of Poverty in Norway - Taryn Ann Galloway (Statistics Norway, Research Department, 2006)
In light of the riots and unrest among immigrants in France during the fall of 2005, the question of how immigrants are faring with respect to a certain minimum in society is both a timely and pertinent question for a number of European countries. In Norway, the prevalence of poverty is alarmingly high among immigrants and stands in stark contrast to the very low poverty rates for the native Norwegian population. Thus, unless the high poverty rates in the immigrant population are just a temporary feature of the immigrants' initial period of adjustment in the host country, poverty among immigrants is a cause for concern in Norway, too. This paper wishes to serve as a complement or extension of previous studies of immigrant adjustment; the study also aims to provide insights on the substantial heterogeneity – observed, unobserved and unobservable – in the immigrant population in Norway.
Keywords: I32; 330; Immigration; Integration; Assimilation